On the Validity of Testudinites sellovii Weiss, 1830 from the Pleistocene of Paso del Catalán (Uruguay, South America) - Vlachos, Evangelos (2018)
The first named extinct turtle species from South America was Testudinites sellovii Weiss, 1830, a tortoise from the Pleistocene of Uruguay. The material consists of isolated plates that come mainly from the plastron (Fig. 1), and originates from the Pleistocene deposits of Passo del Catalán (also known as Paso del Catalán), near river Queguay (or Oueguay) in the area of Paysandú (NW Uruguay). In this note, we present our observations on the syntypes of Museum für Naturkunde, Leibniz-Institut für Evolutions und Biodiversitätsforschung, Berlin, Germany (MfN MB.R.), based on our direct observations on the material.